Takut Akan Tuhan dalam Amsal 1:7 Analisis Teologis dan Pendekatan Epistemologi - Yovianus, Epan; Saputro, Sigit Ani (Shift Key : Jurnal Teologi dan Pelayanan, 2025)
In Proverbs 1:7, this study investigates the concept of “fear of the Lord” as an epistemological paradigm. The comparative method used is combined with theological and philosophical hermeneutical approaches. The text analysis includes the key phrases “fear of the Lord” and “the beginning of knowledge”, which involve the study of Hebrew to explore their contextual, linguistic, and poetic meanings. In addition, this study makes philosophical connections from Louis O Kattsoff's epistemological ideas, including empiricism, rationalism, phenomenalism, intuitionism, and the scientific method. Then, the convergence of thought due to the research shows that the “fear of the Lord” is the basis for understanding wisdom and a unique and relevant epistemological paradigm for understanding how faith, knowledge, and wisdom interact with human life